Remembering popular music's past : memory - heritage - history - Istvandity, Lauren; Baker, Sarah, 1977-; Cantillon, Zelmarie (Anthem Press, 2019)
'Remembering Popular Music's Past' focuses on the transformation of popular music into heritage, and the role of history and memory in this process. The book interrogates diverse examples of the way popular music's past is remembered, with particular emphasis on precarity in the construction, curation, display, negotiation, and perception of popular music's past.